2010
DOI: 10.1007/s11787-010-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Two Semantical Approaches to Paraconsistent Modalities

Abstract: In this paper we extend the anodic systems introduced in Bueno-Soler (J Appl Non Class Logics 19(3):291-310, 2009) by adding certain paraconsistent axioms based on the so called logics of formal inconsistency, introduced in Carnielli et al. (Handbook of philosophical logic, Springer, Amsterdam, 2007), and define the classes of systems that we call cathodic. These classes consist of modal paraconsistent systems, an approach which permits us to treat with certain kinds of conflicting situations. Our interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…First of all, we introduce the syntax of the anodic and cathodic multimodal systems and then show how these classes of multimodal systems can be characterized by means of multi-relational (Kripke-style) models. By using this result, it is also possible to obtain, for the basilar cathodic multimodal systems, a second semantical characterization by means of modal possible-translations semantics, extending the results for the monomodal cases obtained in [BS10].…”
Section: Introductionmentioning
confidence: 58%
“…First of all, we introduce the syntax of the anodic and cathodic multimodal systems and then show how these classes of multimodal systems can be characterized by means of multi-relational (Kripke-style) models. By using this result, it is also possible to obtain, for the basilar cathodic multimodal systems, a second semantical characterization by means of modal possible-translations semantics, extending the results for the monomodal cases obtained in [BS10].…”
Section: Introductionmentioning
confidence: 58%
“…If we agree with this, the notion of probability and its connection to logic are of fundamental importance. Of course, it is also possible to propose a modal paraconsistent approach to probability based on paraconsistent modalities (see [38]), following the lines of [39], but this has to wait for a better motivation.…”
Section: Summary Comments and Conclusionmentioning
confidence: 99%
“…A more intimate relationship between LFIs and their modal versions is investigated by Bueno-Soler in [55], where the so-called anodic modal systems (purely positive modal systems) introduced in [56] are extended by adding certain paraconsistent axioms based on LFIs, defining a class of modal systems called cathodic modal systems. This class consists of modal paraconsistent systems, dealing with certain kinds of conflicting modal situations.…”
Section: Paraconsistent Modalities Consistency and Determinednessmentioning
confidence: 99%
“…This class consists of modal paraconsistent systems, dealing with certain kinds of conflicting modal situations. A semantic interpretation is also given in [55], where it is shown that the cathodic systems can be semantically characterized in two different ways: by means of Kripke-style semantics and by means of modal possible-translations semantics.…”
Section: Paraconsistent Modalities Consistency and Determinednessmentioning
confidence: 99%
See 1 more Smart Citation